A methodological checklist for studies of pleasure and enjoyment responses to high-intensity interval training: Part II. intensity, timing of assessments, data modeling, and interpretation - Ekkekakis, P.; Hartman, M. E.; Ladwig, M. A. (Journal of Sport & Exercise Psychology, 2023)
Recent studies have concluded that high-intensity interval training should be seen as a "viable alternative" to, and may be more enjoyable than, moderate-intensity continuous exercise. If true, these claims have the potential to revolutionize the science and practice of exercise, establishing high-intensity interval training as not only a physiologically effective exercise modality but also a potentially sustainable one. However, these claims stand in contrast to voluminous evidence according to which high levels of exercise intensity are typically experienced as less pleasant than moderate levels. To help researchers, peer reviewers, editors, and critical readers appreciate possible reasons for the apparently conflicting results, we present a checklist that identifies crucial methodological elements in studies investigating the effects of high-intensity interval training on affect and enjoyment. This second installment covers how "high-intensity" and "moderate-intensity" experimental conditions are defined, the timing of assessments of affect, the modeling of affective responses, and data interpretation.